(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
Study of Plant Morphology practicum’s assistant empowerment was conducted to find out the ability of Plant Morphology practicum’s assistants since selection phase, preparation/training phase for peer assisted learning (PAL) implementation, practicum activity and practicum evaluation, and the gain of practicant’s achievement, according to Marzano’s New Taxonomy. This study used mixed methods design that included qualitative data about the practicum assistants’ competencies and quantitative data about the gain of 41 practicant’s achievement. Assistant’s practicum mastery and laboratory skills were reviewed periodically using assistants selection instruments. Assistant’s performance was observed using observation sheets, assistants’ ability in evaluating practicum report was evaluated using report rubrics, and the accuracy of Marzano’s taxon based-practicum questions composed by the assistants was confirmed according to characters of Marzano’s new taxonomy. Practicant’s achievement was found out by pretest-posttest score, student worksheet, work report and exam score. Results showed that assistants’ ability in almost every processing level was already very well develop. The average ability of cognitive, metacognitive and self system of the practicants was also already well-develop. In overall, the PAsPAL program was positively welcomed by most of practicants and every practicum assistants. Studi tentang Pemberdayaan Asisten Praktikum Morfologi Tumbuhan dilakukan untuk mengungkap kemampuan mahasiswa asisten praktikum Morfologi Tumbuhan mulai dari tingkat seleksi, pembekalan untuk melaksanakan Peer Assisted Learning (PAL) pada praktikum, pelaksanaan praktikum, evaluasi hasil praktikum, serta capaian hasil belajar praktikan, ditinjau dari Taksonomi Baru Marzano. Penelitian ini menggunakan desain mixed methods yang melibatkan data kualitatif tentang kemampuan dua mahasiswa asisten praktikum dan data kuantitatif tentang capaian hasil belajar 41 mahasiswa praktikan. Data penguasaan materi praktikum dan keterampilan lab oleh asisten dijaring secara berkala menggunakan instrumen seleksi asisten. Kinerja asisten diobservasi menggunakan lembar observasi, sedangkan kemampuan asisten dalam menilai laporan praktikum menggunakan rubrik penilaian laporan, dan ketepatan soal praktikum bertakson Marzano yang disusun asisten dikonfirmasi berdasarkan karakter masing-masing level pemrosesan taksonomi baru Marzano. Capaian hasil belajar praktikan dijaring melalui pretes-postes, penilaian Lembar Kegiatan Mahasiswa (LKM), laporan praktikum serta skor pra UAS dan UAS. Hasil penelitian menunjukkan hampir semua kemampuan asisten praktikum Morfologi Tumbuhan pada setiap level pemrosesan sudah berkembang dengan sangat baik. Rata-rata kemampuan praktikan pada sistem kognitif, sistem metakognitif dan sistem diri juga berkembang dengan baik. Secara keseluruhan program PAsPAL ditanggapi sangat positif oleh asisten praktikum dan hampir semua praktikan.